The Executive Turnover Risk Premium - Florian S. Peters; Alexander F. Wagner (Tinbergen Institute, 2012)
We establish that CEOs of companies experiencing volatile industry conditions are more likely tobe dismissed. At the same time, industry risk is, controlling for various other factors, unlikelyto be directly associated with CEO compensation other than through dismissal risk. Using thisidentification strategy, we document that CEO turnover risk is significantly positively associatedwith compensation. This finding is important because job-risk compensating wage differentials arisenaturally in competitive labor markets. By contrast, the evidence rejects a simple entrenchmentmodel according to which powerful CEOs have lower job risk and at the same time secure highercompensation.
Keywords: D8; G34; M52; 330; CEO turnover; CEO Compensation; Corporate Governance; Führungskräfte; Lohn; Übernahme; Risikoprämie; Corporate Governance; USA